Reduced adult stem cell fate specification led to eye reduction in cave planarians - Luiza O. Saad; Thomas F. Cooke; Kutay D. Atabay; Peter W. Reddien; Federico D. Brown (Nature Communications)
Abstract Eye loss occurs convergently in numerous animal phyla as an adaptation to dark environments. We investigate the cave planarian Girardia multidiverticulata (Gm), a representative species of the Spiralian clade, to study mechanisms of eye loss. We found that Gm, which was previously described as an eyeless species, retains rudimentary and functional eyes. Eyes are maintained in homeostasis and regenerated in adult planarians by stem cells, called neoblasts, through their fate specification to eye progenitors. The reduced number of eye cells in cave planarians is associated with a decreased rate of stem cell fate specification to eye progenitors during homeostasis and regeneration. Conversely, the homeostatic formation of new cells from stem cell-derived progenitors for other tissues, including for neurons, pharynx, and epidermis, is comparable between cave and surface species. These findings reveal a mode of evolutionary trait loss, with change in rate of fate specification in adult stem cells leading to tissue size reduction.